Teknik Fotografi dan Analisa Semiotika dalam Photoshoot Challenge Romance in Rain INTM Cycle 2 - Aprilia Santika; Maya Purnama Sari (Universitas Merdeka Malang, 2022)
In this study, the author analyzes and discusses photography techniques seen from the photos in the Photoshoot Challenge Romance in Rain INTM Cycle 2 and analyzes the semiotics of the photos based on the theory of Charles Sanders Peirce. Then in the method taken here the author uses a qualitative method, because here the author needs various references from articles, journals, social media, books, and others. Where the photos of the six models analyzed are Helen Hiu, Sarah Tumiwa, Faradina Amalia, Peace Jemima Okechukwu Nnatuanya, Audya Ananta, dan Tiffany Regina. The result of the analysis was obtained which interpreted the pose movements carried out by the model in the photoshoot in the presence of rain falling and it was explained that the techniques used were full shot shooting techniques and how to take photos in rainy conditions. Keywords: Photography, Semiotics, Model